Alchemical Transformation: Building Into Architecture - Ellen Dunham-Jones; Jude LeBlanc (Oz, 1991)
Good buildings like good pictures not only engage our eyes but also our mind. It is through the connection of sensory experience to thought, that craft is transformed into art, and building into architecture.